The crosstalk between mesenchymal stem cells and damaged cartilage in osteoarthritis - Al-Graittee, Satar Jabbar Rahi; Ramasamy, Rajesh (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Human cartilage contains multipotent stem cells, namely mesenchymal stem cells (MSCs) which are progenitors of connective tissue that play homeostatic and reparative roles. Although the major constituent cells in the cartilage are chondrocytes, they possess a limited regenerative ability, and as a result, spontaneous cartilage repair by chondrocytes leads to the synthesis of fibrocartilage. Similarly, MSCs derived from articular cartilage of osteoarthritis patients have demonstrated inadequacy in cartilage repair. The role of MSCs in the pathophysiology of osteoarthritis (OA) is not entirely understood, whether the inflammatory milieu associated with OA joints affects the reparative properties of MSCs or the inherent defects of OA cartilage-derived MSCs impair the proper execution of the required immunosuppressive and reparative functions. Therefore, the current review explores the biological characteristics and features of MSCs derived from physiological state and OA condition with the aim of identifying how OA affects MSC functions as well as the role of MSCs in the pathophysiology of OA.